Hubungan Status Gizi Ibu Hamil Trimester I terhadap Kejadian Stunting pada Bayi Baru Lahir di Puskesmas Kalikotes, Klaten - Astuti, KH. Endah Widhi; Handajani, Sih Rini (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Stunting remains a major public health issue in Indonesia, with a prevalence of 21.6% according to the 2022 Indonesian Nutrition Status Survey (SSGI). Maternal nutritional status during the first trimester is considered a critical factor influencing fetal growth and early childhood nutrition. Objectives: To examine the relationship between first-trimester maternal nutritional status and the incidence of stunting among newborns at Kalikotes Primary Health Center, Klaten, in 2024. Methods: This analytical observational study included all pregnant women in 2024 at the Kalikotes Primary Health Center. Bivariate analysis using the Spearman Rank test was performed to assess the association between maternal BMI, LILA, and haemoglobin levels during the first trimester and newborn stunting. A p-value < .05 indicated statistical significance. Results: Most respondents were 20–35 years old (85.3%) and multigravida. Normal BMI was observed in 42.6%, 25% had no chronic energy deficiency (LILA ≥ 23.5 cm), and 89.7% were non-anaemic. Newborns had an average birth weight of 3057 g and a mean birth length of 48.51 cm. Stunting prevalence was 19.1%. No significant association was found between maternal BMI, MUAC, or haemoglobin levels and stunting. Conclusion: First-trimester maternal nutritional status was not significantly associated with newborn stunting. Stunting is multifactorial, and maternal nutritional indicators alone do not determine its occurrence. Keywords: Stunting, Maternal nutrition, Pregnancy, First trimester, Newborn health, Indonesia